Community assembly of comammox Nitrospira in coastal wetlands across southeastern China - Kam Tang (Applied and Environmental Microbiology, 2023)
Complete ammonia oxidizers (comammox Nitrospira) are ubiquitous in coastal wetland sediments and play an important role in nitriﬁcation. Our study examined the impact of habitat modiﬁcations on comammox Nitrospira communities in coastal wetland sediments across tropical and subtropical regions of southeastern China. Samples were collected from 21 coastal wetlands in ﬁve provinces where native mudﬂats were invaded by Spartina alterniﬂora and subsequently converted to aquaculture ponds. The results showed that comammox Nitrospira abundances were mainly inﬂuenced by sediment grain size rather than by habitat modiﬁcations. Compared to S. alterniﬂora marshes and native mudﬂats, aquaculture pond sediments had lower comammox Nitrospira diversity, lower clade A.1 abundance, and higher clade A.2 abundance. Sulfate concentration was the most important factor controlling the diversity of comammox Nitrospira. The response of comammox Nitrospira community to habitat change varied signiﬁcantly by location, and environmental variables accounted for only 11.2% of the variations in community structure across all sites. In all three habitat types, dispersal limitation largely controlled the comammox Nitrospira community assembly process, indicating the stochastic nature of these sediment communities in coastal wetlands.